Adaptive and robust active vibration control : methodology and tests /: methodology and tests. ([2017]) - Landau, Yoan D, 1938-; Airimitoaie, Tudor-Bogdan; Castellanos-Silva, Abraham; Constantinescu, Aurelian
No abstract available